‘Candidatus liberibacter solanacearum’ protein CKC_05770 interacts in vivo with tomato APX6 and APX7 - Julien Gad Levy; Adwaita Prasad Parida; Junepyo Oh; Azucena Mendoza-Herrera; Brian D. Shaw; Cecilia Tamborindeguy (Scientific Reports)
Abstract Pathogens have evolved mechanisms to manipulate their hosts to facilitate effective colonization and infection. One such mechanism involves the secretion of effectors that interfere with the host immune response. Effectors are typically secreted by dedicated secretion machinery that delivers the protein to the host cell. Liberibacters are intracellular bacterial pathogens that do not encode the typical secretion systems employed to secrete effectors; therefore, other mechanisms might be at play to allow Liberibacters to infect their hosts, such as the secretion of effectors via the sec-secretion system or via non-classical secretion systems. In this study, we datamined the genomes of five Liberibacter pathogens and identified from 66 to 102 putative non-classical secreted proteins encoded. Then, we focused on two predicted non-classical secreted proteins encoded by ‘Candidatus Liberibacter solanacearum’ haplotype B, CKC_05770 and CKC_00930, which showed similarities to non-classical secreted effectors from other Liberibacter species. We evaluated their secretion using alkaline phosphatase assays, if they suppressed programmed cell death or reactive oxygen species accumulation in Nicotiana benthamiana upon transient expression, and whether they could interact with tomato ascorbate peroxidases. We also evaluated if CKC_05770 had a peroxidase activity. Our results suggest that CKC_05770 interacted with tomato ascorbate peroxidases in two in vivo assays but not in vitro. Further, CKC_05770 did not suppress plant immunity nor did it have a peroxidase activity as the ‘Candidatus Liberibacter asiaticus’ homologs did. Therefore, Liberibacter pathogens encode non-classical secreted proteins that could be effectors, but the roles of these proteins need to be validated in each pathosystem.